Reframing Attitudes and Habits: Strategies for Facilitating Learning in Museums Among Students with Disabilities - Simbarashe Shadreck Chitima (The Museum Scholar, 2023)
The majority of students with disabilities are often placed in special classes at formal schools where it is anticipated that they will get additional attention. When field excursions to heritage institutions are organized, students with disabilities are usually left behind, or those who manage to be part of school field trips fail to effectively learn due to various barriers. This study examines the effectiveness of national museums in Zimbabwe in facilitating learning of curriculum content among primary school students with disabilities. This study employed qualitative and phenomenology research approaches. Data was solicited from 320 primary school students with disabilities, eighteen schoolteachers, five museum directors, five museum curators, two display designers, and eight museum tour guides. The study revealed that students with disabilities face attitudinal, physical, and intellectual barriers in accessing national museums for educational purposes. It is concluded that they are few opportunities for students with disabilities to learn curriculum content. Therefore, there is need for museums to embrace an inclusive ethos that include reframing attitudes and habits, develop accessibility policies and facilities in-order to champion the educational and cultural rights of students with disabilities as well afford opportunities to learn curriculum content.